2017
DOI: 10.2147/ott.s121615
|View full text |Cite
|
Sign up to set email alerts
|

Effective BRAF inhibitor vemurafenib therapy in a 2-year-old patient with sequentially diagnosed Langerhans cell histiocytosis and Erdheim–Chester disease

Abstract: Erdheim–Chester disease (ECD) is a rare histiocytic disorder, characterized by the xanthomatous infiltration of tissues by CD68-positive and CD1a-/CD100-negative foamy histiocytes. In childhood, ECD is exceptionally rare, and only a dozen cases have been published so far. The cooccurence of Langerhans cell histiocytosis (LCH) and ECD is even rarer. Here, we report a 2-year-old boy, the youngest patient in the literature so far, who was diagnosed with concomitant BRAF mutation-positive LCH and ECD. In his case,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 23 publications
0
18
1
1
Order By: Relevance
“…BRAF inhibitor Vemurafenib has been used for the treatment of the LCH, and some research showed that combination of Vemurafenib and MEK kinase inhibitors is effective in the treatment of melanomas. 5,31 All these manifested that RAS-RAF-MEK-ERK pathway play an important role in cancer generation.…”
Section: Discussionmentioning
confidence: 99%
“…BRAF inhibitor Vemurafenib has been used for the treatment of the LCH, and some research showed that combination of Vemurafenib and MEK kinase inhibitors is effective in the treatment of melanomas. 5,31 All these manifested that RAS-RAF-MEK-ERK pathway play an important role in cancer generation.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, activating mutations in the BRAF gene have the potential to contribute to clonal cell expansion (9). Indeed, treatment of advanced PLCH with the BRAF inhibitor, vemurafenib, was reported to have resulted in a favorable outcome (10). Interestingly, the same mutation is also observed in 1-3% of non-small cell lung cancer cases, predominantly adenocarcinoma (11).…”
Section: Discussionmentioning
confidence: 99%
“…The amelioration of the PLCH phenotype was associated with a decrease of DC-related cytokine and chemokine levels in the BAL fluid, which further validates the causal role of BRAF VE DCs. Since the discovery of mutations in the RAS/MAPK pathway in LCH, multiple studies have shown that BRAF inhibitors have a beneficial effect in patients with LCH (57,58). However, BRAF inhibition can cause an alternative activation in the MAPK pathway that can lead to significant adverse effects, such as cutaneous squamous cell carcinomas and keratoacanthomas in patients with melanoma (59).…”
Section: Discussionmentioning
confidence: 99%